AN ANALYSIS OF DEIXIS IN DAUGHTER OF THE WOLF MOVIE - Dholiful Hadi; Mansur Mansur; Ni’matul Fauziah (Universitas Muria Kudus, 2023)
Deixis is an utterance of meaning based on the word and phrase in the context of utterance. Deixis is divided into five categories. They are person deixis, place deixis, time deixis, discourse deixis, and social deixis. Deixis is important to be analyzed, because if we read some conversations in the movie or the other literary works, sometimes we will be confused about the meaning in that conversation. It means that deixis is the way to analyze unspeakable context. This study examines types of deixis used in Daughter of the Wolf movie. Research method which was used is qualitative. Type of study is a document analysis. The writer watched Daughter of the Wolf movie and downloaded the scripts to classify type of deixis and the writer did analysis. Based on finding the writer found the type of deixis in Daughter of the Wolf movie, there are four categories of deixis, they are person deixis, place deixis, time deixis, and discourse deixis, and also meaning of deixis used in Daughter of the Wolf movie. The writer suggests, for the future writers who are interesting in doing similar research, this research will give contribution to comprehend the types of deixis and also this research can give inspiration and guidance for the future researchers to be more careful in doing research Keywords: Pragmatics, Deixis, Daughter of the Wolf